Empowering Teachers in Muhammadiyah Boarding School Yogyakarta toward Safer Digital Behavior through Smartphone Security Education - Aris Rakhmadi; Hero Wintolo; Esi Putri Silmina; Dewi Soyusiawaty; Sunardi; Abdul Fadlil (JURPIKAT, 2025)
Abstract: This community-service program was implemented through the Program Pemberdayaan Umat (PRODAMAT) of Universitas Ahmad Dahlan with the aim of enhancing digital literacy and cybersecurity awareness among teachers at Muhammadiyah Boarding School (MBS) Yogyakarta. The activity focused on smartphone account security education through practical steps such as password management, two-factor authentication (2FA), and phishing awareness. A participatory approach was applied through training involving 15 teachers and staff, combining interactive discussions, demonstrations, and pretest–posttest evaluation. The results showed an increase in the average knowledge score from 4.63 to 4.90, digital awareness from 4.05 to 4.45, and intention and safe digital behavior from 4.35 to 4.73. These improvements reflect positive changes in participants’ understanding, awareness, and behavior toward digital security. The program highlights the importance of integrating technological skills with ethical and religious values to promote sustainable digital empowerment in Islamic educational environments.